2006
DOI: 10.1016/j.ijid.2005.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Does a reduction in antibiotic consumption always represent a favorable outcome from an intervention program on prescribing practice?

Abstract: Our results illustrate that a reduction in antibiotic consumption does not always represent a favorable outcome from an intervention program on prescribing practice. Moreover, it may be a sensitive indirect marker of a deficient healthcare condition leading to an increase in in-hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In an Argentine multi-step ABS programme involving training and formulary restriction, antimicrobial consumption could be reduced from 43 to 28 DDD/100 patient-days, resulting in substantial savings (>900.000 USD) over 18 months. During the training period a significant increase in the rate of prescriptions based upon microbiology results (27–63 %) was found, and use of ceftriaxone and carbapenems subsequently more than halved [ 30 ]. The combination of one-on-one education (academic detailing) and special review of orders for either levofloxacin or ceftazidime was also seen as a highly effective method for reducing inadequate antibiotic use.…”
Section: Recommendations Of the Guidelinementioning
confidence: 99%
“…In an Argentine multi-step ABS programme involving training and formulary restriction, antimicrobial consumption could be reduced from 43 to 28 DDD/100 patient-days, resulting in substantial savings (>900.000 USD) over 18 months. During the training period a significant increase in the rate of prescriptions based upon microbiology results (27–63 %) was found, and use of ceftriaxone and carbapenems subsequently more than halved [ 30 ]. The combination of one-on-one education (academic detailing) and special review of orders for either levofloxacin or ceftazidime was also seen as a highly effective method for reducing inadequate antibiotic use.…”
Section: Recommendations Of the Guidelinementioning
confidence: 99%
“…However, reports regarding efforts to reduce antibiotic usage have mainly focused on interventions for in-hospital prescriptions and injectables. [5][6][7][8][9][15][16][17][18][19]24,25 In addition, no reports are examining the effects of interventions on outpatient prescriptions. This is the first report to evaluate the effects of a revised antibiotic formulary on both in-and out-hospital prescriptions to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…16 Other studies have also shown that optimising and reducing antibiotic usage strongly improve pathogens' susceptibility. [17][18][19] These data suggest that reducing antibiotic consumption, especially broad-spectrum antibiotics, is a useful countermeasure against AMR.…”
mentioning
confidence: 95%
“…However, developing countries may go through periods of deficient healthcare conditions that affect the availability of antimicrobial agents. Under these conditions, a reduction in antimicrobial consumption may not represent a favorable outcome[13].…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, a reduction in antimicrobial consumption may not represent a favorable outcome [13]. technologies, and poor adherence to treatment [16].…”
Section: Introductionmentioning
confidence: 99%